2008
DOI: 10.1016/j.jacc.2007.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Frequency of Arrhythmias in Hypertrophic Cardiomyopathy in Relation to Delayed Enhancement on Cardiovascular Magnetic Resonance

Abstract: In this large HCM cohort with no or only mild symptoms, myocardial fibrosis detected by CMR was associated with greater likelihood and increased frequency of ventricular tachyarrhythmias (including NSVT) on ambulatory Holter ECG. Therefore, contrast-enhanced CMR identifies HCM patients with increased susceptibility to ventricular tachyarrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
398
1
16

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(440 citation statements)
references
References 44 publications
(49 reference statements)
22
398
1
16
Order By: Relevance
“…It is an early manifestation of HCM even before hypertrophic remodeling 26. Meanwhile, myocardial fibrosis is a major determinant of SCD, ventricular tachyarrhythmia, left ventricular dysfunction, and heart failure 26, 27, 28. Our results showed that elevated hsCRP predicted an increased risk for adverse outcomes in patients with HCM.…”
Section: Discussionmentioning
confidence: 59%
“…It is an early manifestation of HCM even before hypertrophic remodeling 26. Meanwhile, myocardial fibrosis is a major determinant of SCD, ventricular tachyarrhythmia, left ventricular dysfunction, and heart failure 26, 27, 28. Our results showed that elevated hsCRP predicted an increased risk for adverse outcomes in patients with HCM.…”
Section: Discussionmentioning
confidence: 59%
“…S4, Table S1). An alternative possibility is that electrical uncoupling of CMs results from interstitial fibrosis and heterogeneous loss of connexin43 gap junctions (53)(54)(55). In this regard, IL-1␤-evoked COX-2 expression, depressed in CMs, was increased in fibroblasts harvested from CM-COX-2 KO hearts (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…86 A new superparamagnetic iron oxide probe conjugated to recombinant human annexin has demonstrated diffuse myocardial signal loss in rats treated with doxorubicin, suggestive of apoptosis by CMR. 87,88 Myocardial fibrosis detected as delayed enhancement (DE) by CMR has proven prognostic value in coronary heart disease, 89 and restrictive myocardial diseases including aortic stenosis, 90 hypertrophic cardiomyopathy, 91,92 and the infiltrative diseases of sarcoidosis 93 and amyloidosis. 94 CMR studies in larger populations of patients receiving potentially cardiotoxic agents are needed to see whether the presence of fibrosis detected by gadolinium enhancement identifies a cohort of patients more vulnerable to the cardiotoxic effects of chemotherapy, who may benefit from more frequent and long-term follow-up, and earlier treatment with ACE inhibitors and beta blockade to reduce the incidence and severity of chemotherapy-induced heart failure.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%